An Image-Guided Robotic System for Transcranial Magnetic Stimulation: System Development and Experimental Evaluation - Liu, Yihao; Zhang, Jiaming; Ai, Letian; Tian, Jing; Sefati, Shahriar; Liu, Huan; Martin-Gomez, Alejandro; Kheradmand, Amir; Armand, Mehran (IEEE robotics and automation letters, 2025)
Transcranial magnetic stimulation is a noninvasive medical procedure that can modulate brain activity, and it is widely used in neuroscience, neurology research, and clinical practice. Compared to manual operators, robots may improve the outcome due to their superior accuracy and repeatability. However, there has not been a widely accepted standard protocol for performing robotic TMS using fine-segmented brain images, resulting in arbitrary planned angles with respect to the true boundaries of the modulated cortex. Given that the recent study in TMS simulation suggests a noticeable difference in outcomes when using different anatomical details, cortical shape should play a more significant role in deciding the optimal TMS coil pose. In this work, we introduce an image-guided robotic system for TMS that focuses on (1) establishing standardized planning methods to define a reference (true zero) for the coil poses and (2) solving the issue that the manual coil placement requires expert hand-eye coordination which often leading to low repeatability of the experiments. To validate the design of our robotic system, a phantom study and a preliminary human subject study were performed. Our results show that the robotic method can half the positional error and improve the rotational accuracy by up to two orders of magnitude. The accuracy is proven to be repeatable because the standard deviation of multiple trials is lowered by an order of magnitude. The improved actuation accuracy successfully translates to the TMS application, with a higher and more stable induced voltage in magnetic field sensors and a higher electromyography (EMG) reading in the preliminary human subject study.